To the question of application the structures of basic functions - Milshtein, Oleksandr; Drozda, Ivan; Savytskaja, Yana; Paslon, Volodymyr (Видавництво Львівської політехніки, 2012)
Two cell-matrix structures of basic functions for smoothing by means of a joint processing the data of trajectory measurements with spatial and temporal redundancy were considered.
Keywords: basic functions; cell-matrix structures; spatial and temporal redundancy